Effect of acidic environment on color and translucency of different indirect restorative materials - Abdelaziz A. Omara; Hesham I. Othman; Mohamed F. Aldamaty; Mohamed F. Metwally (BMC Oral Health, 2024)
Abstract Purpose The aim of the current study was to evaluate the effect of simulated gastric acid on the color and translucency of different indirect restorative materials. Materials and methods A total of 36 disc-shaped samples were cut by using an isomet saw and divided into four equal groups (n = 9) according to the material type: Group Z: translucent zirconia (Ceramill® Zolid ht.+ preshade, Amann Girrbach, Koblach, Austria); Group E: lithium disilicate (IPS e.max CAD, Ivoclar Vivadent AG, Schaan, Liechtenstein); Group C: resin nanoceramic (Cerasmart, GC, Tokyo, Japan); Group P: polyether ether ketone (PEEK) (Bettin Zirconia Dentale Italy) veneered with indirect high impact polymer composite (HIPC) (breCAM HIPC, Bredent GmbH & Co. KG, Germany). The samples were immersed in simulated gastric acid (HCl, pH 1.2) for 96 hours at 37 °C in an incubator. The color change (ΔE00) and translucency (RTP00) were measured every 9.6 hours (one-year clinical simulation) of immersion in simulated gastric acid. Results For color change (∆E00) and translucency (RTP00) among the tested materials, there was a highly statistically significant difference (P < 0.001) after every year of follow-up. The color change in both Z and G groups was the lowest after 1 year of acid immersion, followed by that in group H, and the highest change in color was recorded in group P. Conclusion High translucent zirconia is recommended in patients who are concerned about esthetic, especially with acidic oral environment.